Sustainability issues on rice–wheat cropping system - Bhatt, Rajan; Kukal, Surinder S; Busari, Mutiu A; Arora, Sanjay; Yadav, Mathura (International Soil and Water Conservation Research, 2016)
Rice–wheat cropping system (RWCS) of the South Asia is labour-, water-, capital- and energy-intensive, and become less profitable as the availability of these resources diminished. This could be further aggravated with deterioration of soil structure, declining underground water and lesser land and water productivity which ultimately are threat in front of sustainable and profitable RWCS in the region. For improving the profits, production and sustainability of this sequence - a paradigm shift is required. Scientists recommended different resource-conserving technologies (RCTs) viz. zero tillage, laser levelling, irrigation based on soil matric potential, bed planting, direct seeding, mechanical transplanting of rice and crop diversification for this purpose. These technologies are site specific and before selecting any particular RCT for a particular region, soil texture and agro-climatic conditions must be considered. A solitary approach/RCT might not be effective to solve the upcoming issue of producing more food grains with inadequate available water and land. Therefore, an integrated approach is required. But before implementing any approach, different issues relating to RWCS must be discovered, considered and addressed in a holistic manner. In this review, an attempt was made to highlight different issues resulted from the practise of intensive rice–wheat cropping sequence of the region, which must be considered while framing and implementing any integrated approach/project such as conservation agriculture for improving the productions, profits and sustainability of RWCS in the region.